4a-7=9a-3

Simple and best practice solution for 4a-7=9a-3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4a-7=9a-3 equation:


Simplifying
4a + -7 = 9a + -3

Reorder the terms:
-7 + 4a = 9a + -3

Reorder the terms:
-7 + 4a = -3 + 9a

Solving
-7 + 4a = -3 + 9a

Solving for variable 'a'.

Move all terms containing a to the left, all other terms to the right.

Add '-9a' to each side of the equation.
-7 + 4a + -9a = -3 + 9a + -9a

Combine like terms: 4a + -9a = -5a
-7 + -5a = -3 + 9a + -9a

Combine like terms: 9a + -9a = 0
-7 + -5a = -3 + 0
-7 + -5a = -3

Add '7' to each side of the equation.
-7 + 7 + -5a = -3 + 7

Combine like terms: -7 + 7 = 0
0 + -5a = -3 + 7
-5a = -3 + 7

Combine like terms: -3 + 7 = 4
-5a = 4

Divide each side by '-5'.
a = -0.8

Simplifying
a = -0.8

See similar equations:

| 5x+4=-3+2x+16 | | 15x+5=415s+5 | | 1/3x+3/4=5/6x-2 | | 7x=20+3x | | Y-(-3)=(5/6)(x-2) | | 3x(3x+2)=80 | | 3x(3x+2)-80=0 | | 25x/4-5/3=76 | | 5.6-2a+1.4=5.4 | | 350cm=94yd | | (-8)(-2)+11= | | p=20n-12n-200-2.5n | | 4a-3a(a-2)=2(3a-2) | | 2[5x-2(5x+y)]= | | 7(n+9)-6(7n-3)= | | y=.4*-27 | | 4X-24=36 | | y=.4x*27 | | 1/x=2/x+2 | | 3x-12=1x | | 7x+5=37 | | 1/25-5=x | | 322yds=73yds | | X(x-3)=36 | | -0.7x=1.4 | | 4y-8=64 | | 2.35+p=49.25 | | (X/5)=(6/35x)+2 | | v/3+17=30 | | 12=u/2-13 | | 11(q-4)-2(7q+4)= | | u/5=6.25 |

Equations solver categories